Automatic car parking using RFID / Nurul Fatina Yusni - Yusni, Nurul Fatina (Universiti Teknologi Mara Perlis, 2020)
Nowadays, the numbers of cars are consistently rising and parking space becoming a major issue especially in a mall or building. Because of this problem, the project had been developed. It is an automatic car parking using RFID where users can know how many parking spaces are available for users to park their cars and no need to waste their time to find one. This method was developed using a system that allows users to easily enter the parking lot. The tools needed for this project were Arduino, RFID reader and RFID tag or cards, IR sensors, LCD and servo motor. The project’s aims were to design an automatic car parking using RFID and to measure the parking system performance at parking area. Four testing were conducted in this project such as measure the distance range of the RFID reader and IR sensor. There also had network performance testing which measure the signal power and transfer speed. The results show that RFID card can be detected within 20 mm (2 cm) from the RFID reader. IR sensors detection work best when an object position is about 50 mm (5 cm) or 35˚ from the sensors. The good signal power with the distance of 20 mm (2 cm) for 48dB and for the transfer speed with the least response time of 2.0 seconds for 19.2 kBd and 9.6 kBd. This project will give benefit to car users because they can know how many available parking spaces left. The recommendation for future studies are to test the parking monitoring system using IR sensors with LED that will make it easier for the users to find an available parking slot.